인지 행동적 스트레스 관리 프로그램이 응급실 간호사의 사회 심리적 스트레스, 기분 상태, 스트레스 대처방식에 미치는 효과 - 김자현(Ja-Hyun Kim); 한금선(Kuem-Sun Han) (Seuteureseu yeon-gu (Online), 2021)
본 연구는 인지 행동적 스트레스 관리 프로그램이 응급실 근무 간호사의 사회심리적 스트레스, 기분상태, 스트레스 대처방식에 미치는 효과를 검증하기 위해 비동등성 대조군 사전사후 설계로 수행되었다. 본연구는 실험군 39명, 대조군 40명을 대상으로 하여 실험군에게 4주간 7회기에 걸쳐 인지 행동적 스트레스관리 프로그램을 적용하여 효과를 검증한 결과, 인지 행동적 스트레스 관리 프로그램을 적용한 실험군과대조군에서 사회심리적 스트레스, 기분상태, 대처방식에 통계적으로 유의한 차이를 나타내었다. 따라서 인지 행동적 스트레스 관리프로그램이 응급실 간호사의 스트레스 관리에 효과가 있는 것으로 확인 되었다. Background: The study was undertaken to evaluate the effects of a cognitive-behavioral stress management program on psychosocial stress, mood states, and ways of coping with stress for emergency department (ED) nurses. Methods: The study design was a non-equivalent control group with a pre/post design. The study was conducted from July 1, to September 30, 2016. The sample population comprised nurses who work in ED in Seoul, South Korea. The sample size was 79 which included 39 in the experimental group and 40 in the control group. Seven sessions of a program (50 minutes/session) were provided over 4weeks. Data were analyzed using descriptive statistics: the x2-test and the t-test with the SPSS/WIN 21.0 program. Results: There were statistically significant differences in psychosocial stress, mood states, and ways of coping with stress between the experimental group and the control group. However, the sub-hypothesis regarding the degree of using passive coping skills was not supported. Conclusion: The results of this study indicate that a cognitive-behavioral stress management program for ED nurses is effective in reducing psychosocial stress, changing mood states positively, and improving ways of coping with stress effectively. KCI Citation Count: 1